Efektivitas Pemadanan Nomor Pokok Wajib Pajak Dengan Nomor Induk Kependudukan Dalam Upaya Peningkatan Kepatuhan Wajib Pajak Pada Kantor Pelayanan Pajak Pratama Bekasi Utara - Setya Haryati; Yulianto (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The Matching the Taxpayer Identification Number (NPWP) with the Population Identification Number (NIK) is one of the government's policies in an effort to improve taxpayer compliance by integrating the NPWP with the NIK to simplify tax administration so that it is easier for taxpayers to carry out their tax obligations. With the integration of NPWP with NIK, taxpayers will find it difficult to avoid paying taxes so that taxpayer compliance can increase. This research uses a descriptive qualitative method using data obtained from interviews with employees of the North Bekasi Primary Tax Service Office and taxpayers, literature study and observation. This study aims to determine the effectiveness of matching NPWP with NIK in an effort to improve taxpayer compliance at the North Bekasi Primary Tax Service Office. The theory used is the theory of effectiveness according to Richard M Steers. Based on the research that has been conducted, the matching of Taxpayer Identification Numbers with Population Identification Numbers has been effective in increasing taxpayer compliance at the KPP Pratama Bekasi Utara.